PEMBUATAN PEPTON DARI KHAMIR DENGAN ENZIM PAPAIN UNTUK MEDIA PERTUMBUHAN BAKTERI - Fachraniah, Fachraniah; Fardiaz, Dedi; Idiyanti, Tami (Politeknik Negeri Lhokseumawe, 2003)
Peptone can be produced from yeast by enzymatic hydrolysis with papain. The activity of papain used in this experiment against casein is indicated by Vm (2000 unit) and Km (0.8%). The process condition for yeast was [S] = 4.76%, [E] =0.2%, 60 0C, pH 5.8-5.9, 5 hours. The yield of the hydrolysis process of yeast was 18.9%. The peptone obtained was brownish yellow in color with moisture contentof 5%, ash content 7 %, total protein 11%, solubility 98%, amino nitrogen 2.82, and AN/TN ratio = 27.62%. The chromatographic pattern of the peptone using gelfiltration column of Superdex-75 appeared to be the same as that of the commercial pepton. Growth test with E. coli, S. aureus, and B. subtilis showed that yeast peptone could be used as component in media for microbial growth.